2016
DOI: 10.1128/mcb.00338-16
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase 2 and CHOP Restrict the Expression of the Growth Arrest-Specific p20K Lipocalin Gene to G0

Abstract: The activation of the growth arrest-specific (gas) p20K gene depends on the interaction of C/EBP␤ with two elements of a 48-bp promoter region termed the quiescence-responsive unit (QRU). Here we identify extracellular signal-related kinase 2 (ERK2) as a transcriptional repressor of the p20K QRU in cycling chicken embryo fibroblasts (CEF). ERK2 binds to repeated GAAAG sequences overlapping the C/EBP␤ sites of the QRU. The recruitment of ERK2 and C/EBP␤ is mutually exclusive and dictates the expression of p20K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Nuclear CHOP can induce a transient cell cycle arrest in G 1 phase ( 20 ). During ER stress, CHOP also inhibits the growth arrest-specific p20K genes, which are a group of genes that activate reversible G 0 arrest to regulate cell proliferation ( 59 ). Generally, it is known as an important node in the transcription factor network that dominates stress-inducible regulation of specific target genes.…”
Section: Cellular Function Of Chopmentioning
confidence: 99%
“…Nuclear CHOP can induce a transient cell cycle arrest in G 1 phase ( 20 ). During ER stress, CHOP also inhibits the growth arrest-specific p20K genes, which are a group of genes that activate reversible G 0 arrest to regulate cell proliferation ( 59 ). Generally, it is known as an important node in the transcription factor network that dominates stress-inducible regulation of specific target genes.…”
Section: Cellular Function Of Chopmentioning
confidence: 99%
“…Previous studies have shown that transcription mediated by CEBPB is influenced by its heterodimerization with ER stress-related CHOP 24 . Co-IP experiments confirmed that CHOP was associated with CEBPB in MCF-7 and MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…EXFABP is a stress protein that is not only physiologically necessary at the developmental stage but also appears in tissues due to oxidative stress under pathological conditions ( Descalzi Cancedda et al, 2001 ). In chicken embryonic fibroblasts, EXFABP is markedly stimulated by hypoxia-induced growth arrest, alluding that hypoxia is linked to the control of this gene expression and proliferation ( Erb et al, 2016 ). Interestingly, EXFABP is increased in the pectoralis major of both affected and high-feed efficient broilers ( Papah et al, 2018 ; Abasht et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%